Commercial Networks and Cultural Connections in Thrace: Evaluating the Pottery Evidences - Erdem, Zeynep Koçel; Şahin, Reyhan (Journal of Hellenistic Pottery and Material Culture, 2020)
Thrace, nowadays part of Greece, Bulgaria and Turkey, is an important passageway between the Aegean and the Black Seas; the Balkan region and Asia Minor. The archaeological records indicate that Thrace was settled already in the Prehistorical Ages. From the 7th century BC onwards the influence of Western Anatolia and Greece can be followed in the material culture as a result of colonisation movements and commercial activities. After the Persian Invasions in 5th century BC and the Hegemony of Odyrs Dynasty, the region came under the control of Macedonia in 346 BC. During the Roman Empire Thrace received the status of ›Provincia Thracia‹. After the fall of the Western Roman Empire, the Byzantine Empire dominated the region until the 8th century AD. Pottery is one of the most important archaeological category reflecting the cultural traces of the different political phases and providing us with important data about production centers as well as about commercial relations, daily life, religious rituals and burial customs.